Large pseudocyst of pancreas: open surgical drainage by Roux-en-Y cystojejunostomy-an effective physiological drainage strategy: an experience of 28 cases over 18 years - Ray, M. S.; Raval, Aditya; Yadav, Pawan; Patel, Milan; Goyal, Shyam; Patel, Vishal; Ponkia, Darsh; Dhull, Ajay; Manhas, Nishant; Sehrawat, Sachin; Bhasin, Depanshu (International Surgery Journal, 2025)
Background: Pseudocyst pancreas is a complication of acute or chronic pancreatitis. Most pseudocyst <06 cm resolve on their own but large pseudocyst may pose a problem if untreated. Diagnosis is accomplished by USG whole abdomen and CECT whole abdomen. There are different therapeutic strategies: such as endoscopic drainage, percutaneous pigtail external drainage and open surgical internal drainage by Roux-En-Y cystojejunostomy. Methods: This study is the original research prospective study and the cases were prospectively studied in different military hospitals where the lead author served as an army surgeon dealing with 28 cases over 18 years (2006-2024). Over a period of 18 years, we evaluated the result of Roux-en-Y cystojejunostomy in 28 patients diagnosed with pancreatic pseudocysts. They all were >06 to 08 weeks old, >10 cm in diameter (>10 cm is termed as large), situated in the body and tail of the pancreas, with 0.7 to 0.8 cm wall thickness. They all were subjected to standard open surgical drainage (OSD) by Roux-en-Y cystojejunostomy and prophylactic cholecystectomy. Ethical clearance was taken from SGT University gurgaon for cases that were done from 2017 onwards till 2024. Results: Out of 28 patients of pseudocyst pancreas, 06 had SSI, 02 elderly patient with diabetes mellitus had slow recovery. Early enteral feeding within 04 days could be resumed in 11 patients and one had pelvic collection, which was managed by USG guided aspiration. Average hospital stay was 12 days. No morbidity or mortality. Conclusions: We therefore conclude that pancreatic large pseudocyst can be drained effectively and physiologically by open surgical Roux-En-Y cystojejunostomy in any secondary health care center managed by general surgeons.